Synthesis of aryl- and heteroaryl-substituted cyclopentadienes and indenes and their use in transition metal chemistry - Enders, Markus; Baker, Robert W. (Current organic chemistry, 2006)
This article summarizes the synthesis of cyclopentadienes, indenes, cyclopentadienyl ligands and indenyl ligands which have a directly bonded aromatic or heteroaromatic substituent (HCpAr, HIndAr, Cp Ar, IndAr) a. Generally applicable procedures that allow the specific introduction of a variety of aromatic substituents are selected. Section 2.1 describes ring closure reactions of precursors with aromatic substituents which directly lead to cyclopentadienes or indenes. These routes may be used for the synthesis of chiral and enantiopure ligands. In all other synthetic pathways, the formation of the C-C-single bond between the five-membered ring and the aromatic cycle is the essential step. Nucleophilic attack of alkali cyclopentadienides (M-Cp, M = Li, Na, K) on aliphatic halides is an often used reaction which leads to a wide variety of Cp-derivatives with alkyl or functionalised alkyl chains. However, nucleophilic attack on an aromatic ring by cyclopentadienides or indenides is limited to a few activated aromatics such as perfluorobenzene, naphthyl sulfoxides or naphthol sulfonate esters (section 2.2). In order to use the aromatic reagent as the nucleophile, it has to be treated with a Cp+-synthon. However Cp+-derivatives do not exist as isolable species and therefore cyclopentenones are mostly used as Cp+-synthons. β As many cyclopentenone derivatives are available, a large variety of Cp-derivatives can be obtained in this way (section 2.3). Difficulties arise when the 1,4-addition dominates or when the cyclopentenone is deprotonated by the nucleophile. In addition an initially formed HCpAr-derivative may polymerise under the acidic dehydration condition used. Such problems can be avoided by the use of cobaltocenium salts as complex stabilized Cp+ moieties. Nucleophiles can be added, leading to η4-coordinated cyclopentadienes, which may be liberated by oxidation and used in further synthesis (section 2.4). Transition metal catalysed cross-coupling reactions leading to C - C-bond formation between a Cp-ligand and an aromatic substituent have also been described. In such reactions aryl halogenides (ArX, Ar = aryl or heteroaryl, X = halogen) can be coupled with H-Cp, M-Cp, coordinated Cp-ligands or ring metallated Cp-complexes (section 2.5). The polarity of the cross-coupling reaction may also be reversed, as exemplified by the Suzuki coupling of 2-bromoindene with aryl boronic acids. Due to the rigidity of aryl- or heteroaryl-Cp-ligands their metal complexes show in some cases significant differences compared to derivatives with more flexible substituents. Selected examples for this special reactivity are given in section 3.
Gesehen am 18.11.2022